PENGEMBANGAN MEDIA PEMBELAJARAN BERBASIS ICT MENGGUNAKAN MACROMEDIA FLASH PADA MATA PELAJARAN IPA MI/SD - Aquami Aquami; Muhamad Afandi; Andi Putra Sairi (STAI Ma'had Aly Al-Hikam Malang, 2019)
The purpose of this reseach to describe the process of planning or designing, the level of practicality, and the effectiveness of applying ICT-based learning media using Macromedia Flash in class science subjects IV SD / MI. The method used in this study is research and development (R & D) using a four-dimensional model (4-D) including the definition, design, development and dissemination stages. Data collection methods using interviews, observations, expert validation questionnaires and respondents' questionnaires, as well as tests of learning outcomes. Data analysis in this study uses percentage analysis. The results of this study are as follows: (1) The design or design of the media includes the cover page, media, program, material (text, videos, exercises) and tests. (2) The level of practical application very practical average with a total average score of 87.5 on the response of teachers and learners answers obtained Total score 154 with a total average of 90.58 classified as very practical. (3) Effective use of the media is very effective in achieving student learning outcomes. The results of votes accumulated three cognitive, emotional and psychomotor aspects obtained the number of 1423 and an average of 83.70 with both categories. In addition, from the data value of all learners who are known to have reached a value of scientific subjects of completeness at least 100% classified as very effective.